Tính
a)\(\left(5\sqrt{2}+2\sqrt{5}\right)\sqrt{5}-\sqrt{250}\)
b)\(\left(2\sqrt{3}-5\sqrt{2}\right)\sqrt{3}-\sqrt{36}\)
c)\(6\sqrt{\frac{1}{3}}+\frac{9}{\sqrt{3}}-\frac{2}{\sqrt{3}-1}\)
d)\(4\sqrt{\frac{1}{2}}-\frac{6}{\sqrt{2}}+\frac{2}{\sqrt{2}+1}\)
a) \(\left(5\sqrt{2}+2\sqrt{5}\right).\sqrt{5}-\sqrt{250}=5\sqrt{10}+10-5\sqrt{10}=10\)
b) \(\left(2\sqrt{3}-5\sqrt{2}\right).\sqrt{3}-\sqrt{36}=6-5\sqrt{6}-6=-5\sqrt{6}\)
c) \(6\sqrt{\frac{1}{3}}+\frac{9}{\sqrt{3}}-\frac{2}{\sqrt{3}-1}=6\cdot\frac{\sqrt{3}}{3}+\frac{9\sqrt{3}}{3}-\frac{2\left(\sqrt{3}+1\right)}{\left(\sqrt{3}-1\right)\left(\sqrt{3}+1\right)}\)
\(=2\sqrt{3}+3\sqrt{3}-\frac{2\left(\sqrt{3}+1\right)}{3-1}=5\sqrt{3}-2\sqrt{3}-2=3\sqrt{3}-2\)
d) \(4\sqrt{\frac{1}{2}}-\frac{6}{\sqrt{2}}+\frac{2}{\sqrt{2}+1}=4\cdot\frac{\sqrt{2}}{2}-\frac{6\sqrt{2}}{2}+\frac{2\left(\sqrt{2}-1\right)}{\left(\sqrt{2}-1\right)\left(\sqrt{2}+1\right)}\)
\(=2\sqrt{2}-3\sqrt{2}+\frac{2\left(\sqrt{2}-1\right)}{2-1}=-\sqrt{2}+2\sqrt{2}-2=\sqrt{2}-2\)
a, \(\left(5\sqrt{2}+2\sqrt{5}\right)\sqrt{5}-\sqrt{250}\)
\(=5\sqrt{10}+10-\sqrt{250}\)
\(=5\sqrt{10}+10-5\sqrt{10}\)
\(=10\)
b, \(\left(2\sqrt{3}-5\sqrt{2}\right)\sqrt{3}-\sqrt{36}\)
\(=6-5\sqrt{6}-6\)
\(=-5\sqrt{6}\)
c, \(6\sqrt{\frac{1}{3}}+\frac{9}{\sqrt{3}}-\frac{2}{\sqrt{3}-1}\)
\(=\sqrt{\frac{36}{3}}+\frac{9\sqrt{3}}{3}-\frac{2\left(\sqrt{3}+1\right)}{\left(\sqrt{3}-1\right)\left(\sqrt{3}+1\right)}\)
\(=\sqrt{12}+3\sqrt{3}-\frac{2\sqrt{3}+2}{2}\)
\(=2\sqrt{3}+3\sqrt{3}-\frac{2\left(\sqrt{3}+1\right)}{2}\)
\(=2\sqrt{3}+3\sqrt{3}-\left(\sqrt{3}+1\right)\)
\(=2\sqrt{3}+3\sqrt{3}-\sqrt{3}-1\)
\(=4\sqrt{3}-1\)
d,\(4\sqrt{\frac{1}{2}}-\frac{6}{\sqrt{2}}+\frac{2}{\sqrt{2}+1}\)
\(=\sqrt{\frac{16}{2}}-\frac{6\sqrt{2}}{2}+\frac{2\left(\sqrt{2}-1\right)}{\left(\sqrt{2}+1\right)\left(\sqrt{2}-1\right)}\)
\(=\sqrt{8}-3\sqrt{2}+2\sqrt{2}-2\)
\(=2\sqrt{2}-3\sqrt{2}+2\sqrt{2}-2\)
\(=\sqrt{2}-2\)